Adjustment and financing in the developing world : the role of the International Monetary Fund - Killick, Tony (Published by the International Monetary Fund in association with the Overseas Development Institute, London, 1982)
This book, edited by Tony Killick, consists of papers presented at a seminar sponsored jointly by the IMF and the Overseas Development Institute, held in London, England, to discuss the problems facing the developing world in a global environment of high inflation rates and large payments imbalances.